Pengaruh Sistem Pembayaran PBB Online dan Pengetahuan Perpajakan terhadap Kepatuhan Wajib Pajak dengan Sosialisasi Perpajakan Sebagai Variabel Moderasi - Dwi Farradilla; Ridwan Ridwan; Femilia Zahra (AKUNTANSI 45, 2026)
This study aims to analyze the effect of the PBB online payment system and tax knowledge on taxpayer compliance with tax socialization as a moderating variable. This research uses a quantitative approach through a survey method by distributing questionnaires to PBB-P2 taxpayers in Sigi Regency. The sampling technique used slovin’s formula with a total of 388 respondents. Data analysis was conducted using the Partial Least Square (PLS) method with the WarpPLS application.The results indicate that the online PBB payment system has a positive and significant effect on taxpayer compliance. Tax knowledge also has a positive and significant effect on taxpayer compliance. However, tax socialization was not able to moderate the relationship between the online PBB payment system and taxpayer compliance, nor the relationship between tax knowledge and taxpayer compliance. These findings indicate that the ease of the online tax payment system and the level of taxpayer understanding of taxation play an important role in improving taxpayer compliance. This study is expected to contribute to local governments in improving taxpayer compliance through strengthening digital tax payment systems and enhancing tax education for the community.